Influence of Application of Organic Residues of Different Biochemical Quality on Phosphorus Fractions in a Tropical Sandy Soil - Tanabhat-Sakorn Sukitprapanon; Metawee Jantamenchai; Duangsamorn Tulaphitak; Nattaporn Prakongkep; Robert John Gilkes; Patma Vityakon (Agronomy, 2021)
Understanding phosphorus (P) dynamics in tropical sandy soil treated with organic residues of contrasting quality is crucial for P management using organic amendments. This research determined P fractions in a tropical sandy soil under the application of organic residues of different quality, including groundnut stover (GN), tamarind leaf litter (TM), dipterocarp leaf litter (DP), and rice straw (RS). The organic residues were applied at the rate of 10 t DM ha−1 year−1. The P fractions were examined by a sequential extraction procedure. Organic residue application, regardless of residue quality, resulted in P accumulation in soils. For unamended soil, 55% of total P was mainly associated with Al (hydr)oxides. Organic residue application, regardless of residue quality, diminished the NH4F-extractable P (Al-P) fraction, but it had a nonsignificant effect on NaOH-extractable P (Fe-P). The majority of Al-P and Fe-P fractions were associated with crystalline Al and Fe (hydr)oxides. NH4Cl-extractable P (labile P), NaHCO3-extractable P (exchangeable P and mineralizable organic P), HCl-extractable P (Ca-P), and residual P fractions in soil were significantly increased as a result of the incorporation of organic residues. The application of organic residues, particularly those high in ash alkalinity, increase soil pH, labile P, and Ca-P fractions. In contrast, applications of residues high in lignin and polyphenols increase residual P fraction, which is associated with organo-mineral complexes and clay mineral kaolinite.